Assessing Occupational Noise Exposure and Blood Pressure of Cabin Personnel of an Indonesian Diesel Train - Wiwik Budiawan; Pertiwi Andarani; Lare Demetria Agiasti (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2022)
Noise may cause serious health problems, including physiological responses, specifically in the cardiovascular system. This study aims to assess occupational noise exposure and analyze the correlation between occupational noise and blood pressure in cabin and station personnel. The participants were 30 cabin personnel (train drivers) and 30 station personnel. The cabin had a Leq of 90.3 dBA while the noise level at Poncol Station was still below the threshold limit value (TLV), i.e., 75.8 dBA. The noise exposure assessment also included noise exposure profiling. The Chi-square test showed that noise influenced systolic and diastolic blood pressure changes. Furthermore, for train drivers, the t-test showed a difference in systolic and diastolic between before and after the activity. As for station personnel, there was a difference in systolic, but contrarily it was not the case in diastolic. According to the noise profile, the train whistle had the most significant noise level at 120 dBA. Moreover, the use of a train whistle regularly may raise the noise level exposure to cabin staff and even station workers. This study contributes to scientific evidence that occupational noise might affect blood pressure